2006
DOI: 10.1007/11907466_20
|View full text |Cite
|
Sign up to set email alerts
|

Ontology-Based Policy Refinement Using SWRL Rules for Management Information Definitions in OWL

Abstract: Abstract. The goal of ontology-based management is to improve the manageability of network resources through the application of formal ontologies. Prior research work has studied their application to represent the management information definitions, the mapping and merging processes to obtain a semantic integration of those definitions, and the representation of behaviour and policy definitions. Using ontologies allows the additional advantage of integrating, in the same semantic manager, business and service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Policy derivation for access control has been investigated based on resource hierarchies [11], goal decomposition [12], action decomposition [13], data classification [14], ontology [15], etc. In usage control, several enforcements exist at and across different layers of abstraction in various types of systems [2,3,5,[16][17][18].…”
Section: Related Work and Relevancementioning
confidence: 99%
“…Policy derivation for access control has been investigated based on resource hierarchies [11], goal decomposition [12], action decomposition [13], data classification [14], ontology [15], etc. In usage control, several enforcements exist at and across different layers of abstraction in various types of systems [2,3,5,[16][17][18].…”
Section: Related Work and Relevancementioning
confidence: 99%
“…OWL, the Web ontology Language, is proposed as a language for declaring the policies and more of information aspect of choreography. Currently, the OWL is enriched by SWRL [21], as a semantic rule language, to expressing the ontology not only in hierarchal of concepts but also in rule based relation among them.…”
Section: Policy Decompositionmentioning
confidence: 99%
“…We found that such approach requires at least two essential pre-requites. First a dynamic choreography model of services which is capable of altering its elements dynamically without designing the model by hand [21]. Second an approach to impact the policies on the structure and behaviour of choreography model.…”
Section: Introductionmentioning
confidence: 99%
“…Several policy languages exploit ontological semantics to arrange management concepts taxonomically, allowing abstract concepts (higher up) to be used in place of deeper, concrete concepts, so policies can be represented at different levels of abstractions [10], or as a policy-continuum [9], from high-level policies to low-level enforceable policies. The use of semantics for policy refinement is also described in [10] where higher level descriptions of management actions are modelled in an upper ontology and mapped (with the help of rules) to implementationspecific ontologies for management interfaces.…”
mentioning
confidence: 99%
“…The use of semantics for policy refinement is also described in [10] where higher level descriptions of management actions are modelled in an upper ontology and mapped (with the help of rules) to implementationspecific ontologies for management interfaces. In some cases the ontologies are automatically derived from non-semantic management interfaces to interoperate between different types of interfaces [10,11].…”
mentioning
confidence: 99%